Chemodiversity of dissolved organic matter in produced water correlates with the microbial community in fifteen shale gas wells - Hassan Ramadan; Yufei Ji; Ling Wang; Qiyue Kuang; Zhaoji Zhang (Desalination and Water Treatment)
Interactions between DOM and microbial communities in produced water (PW) from shale gas wells is still lacking. This work examined PW from 15 wells in China's first shale gas field using high-throughput microbial analysis and ultra-high resolution DOM compositional analysis to determine microbial diversity, DOM chemodiversity, and their interaction. Results showed the instability of most organic compounds, the composition of the detected semi-volatile organic compounds varied significantly among the samples, and the strongly polar organic compounds were aliphatic. PW samples had higher H/Cwa, lower O/Cwa, and lower double bond equivalent values than river organic matter, indicating more saturated, less polarized, and fewer relative oxygenated compounds. The similarity in CHOS composition in most PW samples was probably due to the addition of similar sulfur-containing chemicals during extraction. The microbial diversity in PW was not rich compared with that in other samples, such as soil and activated sludge. Despite limited microbial diversity, aerobic, microaerophilic and anaerobic bacteria and methanogenic archaea coexisted. Correlation analysis revealed Euryarchaeota could be involved in the degradation of sulfur-containing organics and the accumulation of aromatic compounds. This correlation analysis can provide an in-depth understanding of the transformation of DOM and its interactions with microorganisms in shale gas PW.